2019
DOI: 10.9734/ajeba/2019/v11i330133
|View full text |Cite
|
Sign up to set email alerts
|

Board Independence and Financial Performance of Deposit Money Banks in Nigeria and Canada

Abstract: Introduction: In current eras, supervisory bodies have interceded in the operations of Deposit Money Banks. This is because they are confronted with plethora of problems such as overexpansion; corruption of bank officers, inappropriate risk management and these resulted to poor financial performance. Aims: The present study aims to focus on the link amid board independence and financial performance of Deposit Money Banks as well as providing a comparative view by focusing on Nigeria and Canada. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…Finally, board independence is positively and significantly related to firm performance. This result is consistent with the findings of Ayodeji and Okunade (2019), Bouteska (2020), Osman and Samontaray (2022) and Handa (2022) that financial institutions with more independent directors on the board tend to have a high firm performance. This result corroborates both the agency theory and the resource dependency theory that more independent directors on the board improve the board's role in monitoring and controlling the management, which ultimately makes the company’s operations more efficient and increases its performance.…”
Section: Results Analysis and Discussionsupporting
confidence: 92%
“…Finally, board independence is positively and significantly related to firm performance. This result is consistent with the findings of Ayodeji and Okunade (2019), Bouteska (2020), Osman and Samontaray (2022) and Handa (2022) that financial institutions with more independent directors on the board tend to have a high firm performance. This result corroborates both the agency theory and the resource dependency theory that more independent directors on the board improve the board's role in monitoring and controlling the management, which ultimately makes the company’s operations more efficient and increases its performance.…”
Section: Results Analysis and Discussionsupporting
confidence: 92%
“…Mwaura (2017) uncovered that board independence showed a substantial favorable association among board's qualities and the company's profit. Ayodeji et al (2019) unraveled that independence of boards has a very good impact on deposit-making institutions' financial health. Andow et al (2019) equally found that independence of boards has an insignificantly favorable impact on the institutions' financial performance.…”
Section: Board Independence and Profitability Of Manufacturing And Al...mentioning
confidence: 99%
“…In this connection,Sanyaolu et al (2019) investigated the specific and macroeconomic factors that affected the profitability of 10 listed deposit money banks on the Nigerian Stock Exchange. Pham et al (2020) examined 10 Vietnamese banks Okere et al (2018). revealed that credit and liquidity risk have strong beneficial impact on the banks' profitability.…”
mentioning
confidence: 99%